Perceptual Speech Outcomes After Early Primary Palatal Repair in Ugandan Patients With Cleft Palate. (August 2021) - Bettens, Kim; Bruneel, Laura; Alighieri, Cassandra; Sseremba, Daniel; Musasizib, Duncan; Ojok, Isaac; Hodges, Andrew; Galiwango, George; Adriaansen, Anke; D'haeseleer, Evelien; Vermeersch, Hubert; Van Lierde, Kristiane
Objective: To provide speech outcomes of English-speaking Ugandan patients with a cleft palate with or without cleft lip (CP±L). Design: Prospective case–control study. Setting: Referral hospital for patients with cleft lip and palate in Uganda. Participants: Twenty-four English-speaking Ugandan children with a CP±L (15 boys, 9 girls, mean 8.4 years) who received palatal closure prior to 6 months of age and an age- and gender-matched control group of Ugandan children without cleft palate. Interventions: Comparison of speech outcomes of the patient and control group. Main Outcome Measures: Perceptual speech outcomes including articulation, resonance, speech understandability and acceptability, and velopharyngeal composite score (VPC-sum). Information regarding speech therapy, fistula rate, and secondary surgery. Results: Normal speech understandability was observed in 42% of the patients, and 38% were judged with normal speech acceptability. Only 16% showed compensatory articulation. Acceptable resonance was found in 71%, and 75% of the patients were judged perceptually to present with competent velopharyngeal function based on the VPC-sum. Additional speech intervention was recommended in 25% of the patients. Statistically significant differences for all these variables were still observed with the control children ( P < .05). Conclusions: Overall, acceptable speech outcomes were found after early primary palatal closure. Comparable or even better results were found in comparison with international benchmarks, especially regarding the presence of compensatory articulation. Whether this approach is transferable to Western countries is the subject for further research.